The 8-item Morisky medication adherence scale: validation of a Portuguese version in HIV patients. (30th September 2020) - Aguiar, A; Piñeiro, C; Serrão, R; Duarte, R
Abstract: Background: Antiretroviral therapy (ART) has the most effective treatment for people with HIV, but its effectiveness depends on the individual medication adherence. Morisky Medication Adherence Scale (MMAS-8) is one of the most widely used scales to assess patient adherence. Thus, we aimed to validate a Portuguese version of MMAS-8 and determine its psychometric properties in HIV positive patients. Methods: A cross-sectional survey was conducted in Centro Hospitalar Universitário São João (Porto, northern Portugal) at the infectious diseases department. After authorization to use the scale - granted by the author - and, a standard forward-backwards procedure to translate MMAS-8 to Portuguese, the questionnaire was applied to 233 patients with HIV doing ART. Reliability was assessed using Cronbach's alpha and test-retest reliability. Three levels of adherence were considered: 0 to < 6 (low), 6 to < 8 (medium), 8 (high). Results: In the studied sample, the mean age was 45.03 years (SD = 11.63), 80.3% men, 19.3% women and 1 transgender, and 53.8% had ≤9 years of education. The mean number of prescribed ART per patient was 1.76. The mean score for the medication adherence scale was 7.29 (SD = 6.74). For the reliability analysis, 12 patients were excluded due to missing data (n = 221). Regarding the level of adherence, 22.5% were low adhering, 71.6% medium and 5.9% high. Corrected item-total correlations showed that 1 item does not correlate very well with the overall scale and was dropped. Scale reliability analysis for the remaining 7 items revealed an overall Cronbach's alpha of 0.661. Women had a protective effect on adherence (OR = 0.31;95%CI:0.15-0.66). Number of years doing ART, age of participants, and type of residence didn't show to be correlated with adherence. Conclusions: MMAS-8 is a reliable and valid measure to detect patients at risk of non-adherence. A satisfactory Cronbach's alfa (0.661) was obtained. In general, adherence to medication was medium or high. Key messages: This scale can be applied nationwide in other different hospitals, as it could serve as a tool for measuring adherence to ART that can allow for better health care to the ones that are low adhering. A Portuguese version of the MMAS-8 was created for measuring adherence to ART that maintained a similar structure to the original MMAS-8 and good psychometric properties.